2007
DOI: 10.1007/s11104-007-9410-6
|View full text |Cite
|
Sign up to set email alerts
|

Field decomposition of transgenic Bt maize residue and the impact on non-target soil invertebrates

Abstract: Genetically modified Bacillus thuringiensis Berliner (Bt) maize (Zea mays L.) expressing Cry toxins against various target pests is now grown on more than 16 million hectares worldwide, but its potential effects on the soil ecosystem need to be further investigated. In an 8-month field study, we investigated the effects of Bt maize expressing the Cry1Ab protein on both the soil community and maize residue decomposition. We used litterbags with three different mesh sizes (20, 125, and 5,000 μm) to investigate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 63 publications
5
52
0
Order By: Relevance
“…Additionally, 86% (n = 187) of the streams contained some form of maize detritus, such as cobs and stalks, in addition to maize leaves. However, in the case of cobs and stalks, we cannot be certain they originated from the 2006 crop year because they decompose more slowly than leaves, the latter of which were most likely from 2006 based on maize leaf decomposition studies (6,23). Stream sites containing maize leaves were prevalent and randomly distributed across the stream network ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, 86% (n = 187) of the streams contained some form of maize detritus, such as cobs and stalks, in addition to maize leaves. However, in the case of cobs and stalks, we cannot be certain they originated from the 2006 crop year because they decompose more slowly than leaves, the latter of which were most likely from 2006 based on maize leaf decomposition studies (6,23). Stream sites containing maize leaves were prevalent and randomly distributed across the stream network ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Litter-bag experiments with Bt-maize (Bt11) reported by Zwahlen et al (2007) did not reveal major changes in the decomposition rate of Bt-maize residues. Similarly, but for MON810 instead of Bt11, various studies found no evidence for any effect related to the genetic modification when examining the decomposition rate of Bt-maize (Griffiths et al, 2007a,b;Hönemann et al, 2008;Lehman et al, 2008;Tarkalson et al, 2008).…”
Section: Gmo Panel Assessmentmentioning
confidence: 88%
“…by Birch et al (2007) and currently by Arias-Martín et al (2016). In general, no severe side-effects on soil animal (Zwahlen et al, 2007;Hönemann et al, 2008) or collembolan (Marvier et al, 2007;Comas et al, 2014) populations and coenosees were found in the field.…”
Section: Introductionmentioning
confidence: 85%